Yeast cell morphology and sexual reproduction: a short overview and some considerations = Morphologie des cellules de levure et la reproduction sexuelle : apercu̦ général et quelques considérations - Knop, Michael (Comptes rendus biologies, 2011)
Over the decades, basic research in life sciences has profited greatly from the study of the small unicellular fungal species Saccharomyces cerevisiae. This yeast turned out to be key for the identification and understanding of molecular mechanisms that underlay the basic functions of all eukaryotic cells. These include, but are not limited to, the regulatory mechanisms behind cellular reproduction (cell cycle control), cellular morphogenesis (cell polarity, cytoskeleton and membrane trafficking) and the management of cellular information (chromosome biology, transcription and translation). Rapid access to genomic information of many yeast species, combined with bioinformatics analyses, provide information on the evolutionary history of yeasts and the molecular ancestry of their constituents. The availability of a comprehensive list of experimental procedures for these organisms presents now a unique opportunity to learn about variations of molecular processes on an evolutionary scale. Yeast cell morphology is another interesting factor, since cellular shapes influence the interactions with the environment on all levels. In this overview article I provide a short summary of the relevant aspects of yeast cell morphology, in particular in relation to one of the most influencing processes, cellular reproduction by mating and meiosis.